La promesa unilateral y la responsabilidad civil - Huanco Piscoche, Henry (2020)
The unilateral promise is a legal institution widely used in day to day practice, mainly to locate misplaced items, missing persons, gather information to find the whereabouts of a certain criminal, or, in the business realm, in the expenditure of promissory notes; however, it has not been dutifully analyzed by the national legal doctrine, opposed to what happens in comparative doctrine. Therefore, in this article we develop a thorough analysis of its historical precedents, its regulation in the most influential civil codes, how it has been treated by the Peruvian civil codes, the types of “true” unilateral promises and the regulation of the public liability derived from the breach of a unilateral promise.